Recurrent myxoid liposarcoma of thigh - K.B., Vismaya; Rashid, Rihan (International Journal of Research in Orthopaedics, 2023)
We are presenting the case of a 78 year old man who presented to our out-patient clinic with a history of a recurrent mass over the anteromedial aspect of the left thigh. The aim of this case report is to study the clinical, radiological findings, diagnosis and surgical management of a well differentiated liposarcoma.